ANALYSIS OF THE EFFECT OF FINANCIAL DISTRESS, COMPANY SIZE, INVENTORY ACTIVITIES AND PROFITABILITY ON AUDIT DELAY - Sihombing, Tanggor; Ka Hing, Chan (2021)
Audit report lag or audit delay can reflect the timeliness of information conveyed by a company which will have an impact on increasing the level of uncertainty of an investor's decision based on the information provided. This study aims to examine empirically the effect of financial distress, firm size, inventory activity and profitability on audit delay. The population studied in this study were companies registered on the S&P Global Market Intelligence Platform from 2017 to 2019. The sample used in this study was taken using purposive sampling in order to obtain samples that match the criteria. The sample in this study amounted to 303 observations. The results of research through multiple linear regression indicate that financial distress has no effect on audit delay. In addition, the results of this study also indicate that firm size, inventory activity and profitability have a negative effect on audit delay.